Making poverty: a history of on-reserve housing programs, 1930-1996 - Olsen, Sylvia (2016)
While few people would say that Canada has done a good job of housing its poor citizens, this discussion goes beyond problems of housing the poor. In this dissertation I draw from government records to uncover how, between the 1930s and 1990s, the Indian Department created and oversaw a failed housing system on reserves across the country - one decision at a time. While housing is usually seen to be a result of poverty I argue that during this time the practices and policies of the Indian Department were active participants in making Indigenous people and First Nations communities poor. As a consequence of the persistent housing crisis on reserves in Canada Indigenous people suffered not only from living in substandard dwellings but also from the indignity and shame that comes from the association Canadians have made between the poor conditions of on-reserve housing and the personal characteristics of its occupants. What most people do not know is how it is that on-reserve housing remained in crisis for so long. On-reserve housing is something we have done not something we have studied. While federal government reports have charted the number of houses on reserves and their physical condition, no one has examined the history of government programs or how they were delivered until now. Recognizing that my study was not designed to recommend solutions, but believing that we cannot fix a problem until we know it, I am convinced that this dissertation provides the background information future academics will need to tell a different story about housing on reserves. And with a different story we will be better prepared to make fundamental changes needed to the way housing is delivered on reserves. Graduate